Branched polydiene, rubber composition based thereon
By using catalyst composites such as lanthanide compounds in the rubber kneading step for conjugated diene polymerization, combined with branching agents and low molecular weight polymer modification techniques, the problems of uniform distribution and energy consumption of liquid rubber are solved, and the processability and elastic-hysteresis characteristics of the rubber composition are improved.
Patent Information
- Application Number
- CN201980103047.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-12-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2039-12-20
AI Technical Summary
In the rubber kneading step, the uniform distribution of the liquid rubber is difficult to ensure, and additional energy consumption is required, affecting the processability and physical and mechanical properties of the rubber composition.
By preparing a catalyst composite, it comprises a lanthanide compound, an organoaluminum compound, a conjugated diene and a halogen-containing component, polymerizes the conjugated diene in the presence, and postpolymerization modification is performed using a branching agent, and finally a low molecular weight polymer is introduced as a plasticizer, degassing and drying.
The preparation of branched polydienes is achieved with improved processability and filler distribution, and the rubber composition based on the polydiene exhibits good elastic-hysteresis characteristics.
Smart Images

Figure GDA0005043069090000211 
Figure GDA0005043069090000231 
Figure GDA0005043069090000241
Abstract
Description
Technical Field
[0001] The present invention relates to the production of synthetic polymers used in the manufacture of tires and rubber technical products in the electrical industry and other fields.
[0002] In particular, the present invention relates to a method for producing branched polydiene by polymerization of conjugated diene, the method comprising the steps of: preparing a catalyst composite comprising a lanthanide compound, an organoaluminum compound, a conjugated diene and a halogen-containing component; polymerizing the conjugated diene in the presence of the catalyst composite; post-polymerization modification using at least one branching agent selected from halogen-containing compounds, phosphorus-nitrogen compounds, or mixtures thereof; termination, introducing a plasticizer into the polymer, wherein the plasticizer is a low molecular weight polymer having a molecular weight of 1500 g / mol to 50,000 g / mol, degassing and drying the polymer. In yet another aspect, the present invention relates to a method for producing a rubber composition based on the above branched polydiene.
[0003] The branched polydiene prepared according to the present invention has a Mooney viscosity index of 40 Mooney Units (MU) to 49 Mooney units, a polydispersity index in the range of 2.16 to 2.60, a branching index characterized by the mechanical loss tangent tgδ (1200%) of about 4.7 to about 5.3, and a content of 1,4-cis units of 96.0% to 98.0%. The rubber composition based on the prepared polydiene is characterized in that the Mooney viscosity of the rubber composition is low and exhibits good elastic-hysteresis properties. Background Art
[0004] Today, in order to increase competitiveness, it is extremely important for rubber producers to have advantages in the properties considered in the environmental labeling of tires. In the contribution of this goal, the rolling resistance index, which accounts for 20% to 30% of the fuel consumption of automobile transportation, must be optimized. A reduction in rolling resistance will not only reduce fuel consumption, but also lead to a reduction in CO2 emissions.
[0005] The emergence of a wide range of low molecular weight polymers (so-called liquid rubbers) on the market makes it possible to obtain winter non-studded tires with improved grip in winter conditions. Some companies have used liquid rubber as a reinforcing additive in tread compounds. In tests, the treads thus obtained showed high plasticity and remained flexible even at low temperatures and also showed improved grip on ice.
[0006] Patent RU2394692 (SUMITOMO RABBER INDASTRIES, LTD (JP), 07.20.2010) describes the production of a rubber composition for the sidewall of a pneumatic tire, the rubber composition comprising: 100 parts by mass of a first rubber component, the first rubber component consisting of 30% to 70% by mass of natural rubber and 70% to 30% by mass of epoxidized natural rubber; 20% to 60% by mass of silica; and 3% to 60% by mass of a second rubber component consisting of a liquid rubber and a vulcanizing agent. This provides an "eco-type" pneumatic tire with improved durability (improved heat resistance, crack resistance, ozone resistance).
[0007] However, the introduction of liquid rubber during the step of mixing the rubber does not ensure its uniform distribution in the polymer matrix and, moreover, requires additional energy consumption. In addition, according to this patent, only liquid polyisoprene rubber (natural rubber) is used.
[0008] It is known to use liquid polydiene as part of the rubber composition. Patent EP2082899 (CONTINENTALAG (DE), 18.05.2011) describes a method for producing a rubber composition consisting of 5 to 50 parts by mass of a liquid low-viscosity polymer. The obtained mixture exhibits improved elasticity at low temperatures and improved tensile modulus at 300% elongation.
[0009] Liquid rubber is also introduced during the rubber mixing step, and there is no mention in the patent of any improvement in the physical and mechanical properties and elastic hysteresis properties of the rubber mixture.
[0010] A method for improving the wear resistance of a rubber composition for manufacturing a tire tread using functionalized liquid polybutadiene is known from US8975324 (RANDALL AMY M (US), AGARWAL SHEEL P (US), HERGENROTHERWILLIAM L (US), BRIDGESTONE CORP (JP), 10.03.2015). The rubber composition according to the invention comprises a conjugated diene polymer or copolymer; at least one filler; an amount of 2 to 10 phr of liquid polybutadiene functionalized with an unsaturated carboxylic acid anhydride; 0.2 to 5 phr of zinc oxide; and 1 to 100 phr of processing oil. In the patent, liquid rubber is introduced at the step of mixing rubber, and a comparison of a rubber composition having liquid rubber with a rubber composition based on an oil-extended polymer shows that the Mooney viscosity of the former is 10% to 28% higher than that of the latter, which indicates poor processability; in addition, the vulcanization rate of the rubber composition having liquid rubber is 1.5 to 2 times lower.
[0011] As disclosed in US6472461 (BRIDGESTONE CORP (JP), 29.10.2002), the rubber composition prepared is composed of: 1) a rubber component, comprising a) at least one natural or synthetic diene rubber, b) a low molecular weight polybutadiene in an amount of 6% or more based on the rubber component, such as an average molecular weight of 5,000 to 30,000 measured by gel permeation chromatography based on the molecular weight of polystyrene, and a 1,4-cis structure content of 60% to 98%; 2) polyethylene short fibers having an average length of 10 mm or less; and 3) a foaming agent. The invention relates to a method for producing a pneumatic tire exhibiting improved braking performance on ice.
[0012] The inventors do not provide data on the parameters that are very important to tire manufacturers - wear of the rubber, elastic-hysteresis properties at 60° C. and strength properties.
[0013] RU2429252 (BRIDGESTONE CORP (JP), 20.09.2011) also describes a method for introducing a low molecular weight polymer during the step of mixing rubber. The rubber mixture is prepared by mixing 1 to 60 parts by weight of a low molecular weight conjugated diene-based polymer (B) per 100 parts by weight of the rubber component (A) mixed with (B), wherein the low molecular weight conjugated diene-based polymer (B) has a weight average molecular weight of greater than 30,000 to not more than 200,000 as measured by gel permeation chromatography and converted to polystyrene. The rubber component (A) contains natural rubber and / or polyisoprene rubber, and is optionally at least one rubber selected from styrene-butadiene copolymer rubber, polybutadiene rubber and isobutylene isoprene rubber. The composition according to the invention has excellent processability and heat resistance during production, high storage elastic modulus and small loss tangent (tgδ).
[0014] However, the introduction of liquid rubber during the rubber compounding step does not ensure its uniform distribution in the polymer matrix.
[0015] It is known that during the post-polymerization modification and polymerization modification with maleic acid (maleic) fragment, the active center (growing macromolecule) interacts with the carbonyl group, and then the molecular parameters and the plasticity-elasticity characteristics of polybutadiene change. In addition, new phenomena have also been found. Especially, when directly introducing modifiers (polymerization modification) into the final catalyst complex, modifiers not only interrupt the polymerization process, but also provide the result close to post-polymerization modification (VLZolotarev, On the mechanism ofthe process of post-polymerization modification of neodymium 1,4-cis-polybutadiene, J. "Vysokomolekulyarnye soedineniya" [High Molecular Compounds], the 3rd phase, pages 3 to 5, 2015).
[0016] However, the use of maleated polybutadiene alone for modification, regardless of the time of its introduction, does not impart optimal performance characteristics to the rubber.
[0017] A promising direction is the postpolymerization modification of low molecular weight polymers, which has an effect on the properties of 1,4-cis-polybutadiene and rubber compositions based thereon.
[0018] The process for preparing polybutadiene as disclosed in US7112632 (POLIMERI EUROPA SPA (IT), 26.09.2006) is closest to the essence of the present invention. According to this process, the process for preparing polybutadiene comprises: (a) polymerization of butadiene; (b) treating the polymer solution obtained when completing step (a) with a coupling agent selected from the following: (i) unsaturated natural oils; (ii) butadiene and / or isoprene oligomers; (iii) copolymers of butadiene and / or isoprene with vinyl aromatic monomers; the unsaturated groups (unsaturation) present in compounds (i) to (iii) are at least partially replaced by groups selected from epoxides, anhydrides and esters; (c) recovering the low-branching polybutadiene obtained when completing step (b). According to this patent, the polymer obtained has a low branching content.
[0019] However, it is known that good processability of rubber compounds is ensured by using branched polymers. The patent does not contain any information about the homogeneity of the filler distribution in the polymer matrix, nor about the improvement of the wear resistance and processability of the polymer obtained. Summary of the invention
[0020] The object of the present invention is to improve the processability of polymers in the rubber compounding step.
[0021] The object is solved by developing a method for preparing branched polydiene by polymerization of conjugated diene, the method comprising: preparing a catalyst complex, the catalyst complex comprising a lanthanide compound, an organoaluminum compound, a conjugated diene and a halogen-containing component; polymerizing the conjugated diene in the presence of the catalyst complex; post-polymerization modification with at least one branching agent selected from halogen-containing compounds, phosphorus-nitrogen compounds or mixtures thereof; terminating, introducing a plasticizer into the polymer, wherein the plasticizer is a low molecular weight polymer with a molecular weight of 1500 g / mol to 50,000 g / mol, degassing, separating and drying the polymer.
[0022] The technical result of the present invention is the preparation of such branched polydienes characterized by a Mooney viscosity of about 40 Mooney units (MU) to about 49 Mooney units, and a branching index characterized by the mechanical loss tangent tgδ (1200%) of about 4.7 to about 5.3. The polydienes prepared according to the present invention have improved processability, improved distribution of fillers in the polymer matrix, and the rubber compositions based on said polydienes are characterized by improved elastic-hysteresis properties (i.e., Mooney viscosity ML (1+4), MU, Payne effect Δ (G'1%-G'50%), kPa, tgδ at 10% deformation at 60°C).
[0023] According to the invention, the modification is carried out by using at least one branching agent selected from halogen-containing compounds, phosphorus-nitrogen compounds or mixtures thereof.
[0024] Compounds used as the branched halogen-containing compound include thionyl chloride, diphenyltin dichloride, phenyltin trichloride, triphenyltin chloride, dibutyltin dichloride, butyltin trichloride, tin tetrachloride, and silicon tetrachloride.
[0025] Phosphorus-nitrogen compounds are compounds having a repeating unit (-P=N-) n A compound of a chemical structure wherein n is an integer from 3 to 24.
[0026] Branching agents interact with polymers at the active ends of their polymer chains. Branching agents affect the Mooney viscosity and branching coefficient of polymers, and affect changes in molecular weight characteristics of polymers such as number average molecular weight Mn, weight average molecular weight Mw, polydispersity Mw / Mn, etc.
[0027] Plasticizer (softener) is a substance that promotes polymer processing when introduced into a polymer. In this case, the plasticizer does not interact with the polymer chemistry; only physical mixing occurs. Plasticizer is usually added during the step of mixing rubber. During the step of mixing rubber, there is a classical liquid plasticizer in the formula of the rubber mixture to allow the homogenization of the rubber mixture to a certain extent; however, in most cases, a significant dosage (averaging 15 weight portions) adversely affects the complex physicochemical properties of the resulting vulcanized rubber.
[0028] The distinguishing feature of the present invention is the introduction of a plasticizer in the form of a solution in an inert organic solvent during the step of preparing the polymer. This technology allows the use of low doses of plasticizer (in an amount 6 or more times lower than that introduced during the step of mixing the rubber) and increases the processability by at least 6 to 10% compared to a polymer that has undergone only post-polymerization modification without the addition of a plasticizer.
[0029] According to the present invention, a plasticizer is used in the step of preparing the polymer, wherein the plasticizer is a low molecular weight polymer having a molecular weight of 1,500 g / mol to 50,000 g / mol. Unfunctionalized low molecular weight polybutadiene, polybutadiene functionalized with maleic anhydride or triethoxysilane, and unfunctionalized low molecular weight polyisoprene and polyisoprene functionalized with maleic anhydride are preferably used as such plasticizers.
[0030] Non-functionalized low molecular weight polybutadiene and polybutadiene functionalized with maleic anhydride or triethoxysilane are most preferred as plasticizers because they have the same microstructure as neodymium polybutadiene.
[0031] Exemplary commercially available plasticizers are isoprene homopolymers (e.g., LIR-30, LIR-50 produced by Kuraray Co., Ltd.), maleic anhydride-modified polyisoprene (e.g., MIP-004 Kuraray Co., Ltd.), non-functionalized low molecular weight ("liquid") polybutadiene (e.g., Polyvest 130 from Evonik), maleic anhydride-functionalized polybutadiene (e.g., Polyvest 75MA from Evonik or Ricon 130 MMAA8, Ricon 130 MMAA10, Ricon 130 MMAA13, Ricobond 1031, Ricobond 1731, Ricobond 2031, Ricobond 3031 from Cray Valley, 1756) or triethoxysilane-functionalized polybutadiene (eg Polyvest EP ST-E 60, Polyvest EP ST-E 80, Polyvest EP ST-E 100 from Evonik). The properties of the plasticizers (liquid rubbers) used according to the invention are shown in Table 2.
[0032] The dosage of the plasticizer according to the present invention is 0.5% to 5.0% by mass based on the polymer, the preferred dosage is 0.7% to 2.0% by mass, and the most preferred dosage of the plasticizer according to the present invention is 0.8% to 1.5% by mass. The dosage of the plasticizer above the limited range causes the Mooney viscosity of the polymer to be significantly reduced, and causes the conditional tensile strength in the rubber composition to be reduced. A dosage less than 0.5% by mass cannot cause improvements in the properties of the polymer and the rubber composition based thereon.
[0033] The catalyst composite used according to the present invention comprises a lanthanide compound, an organoaluminum compound and a halogen-containing component. Compounds used as lanthanide compounds include compounds containing at least one lanthanide atom of the following: neodymium, lanthanum, cerium, praseodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium. Neodymium is preferred.
[0034] Compounds containing lanthanide elements include, but are not limited to, carboxylates, organic phosphates (particularly alkyl phosphates and aryl phosphates), organic phosphonates (particularly alkyl phosphonates and aryl phosphonates), organic phosphinates (particularly alkyl phosphinates and aryl phosphinates), carbamates, lanthanide xanthates, β-diketonates, halides, oxyhalides, and alcoholates.
[0035] Neodymium carboxylates include neodymium formate, neodymium acetate, neodymium acrylate, neodymium methacrylate, neodymium valerate, neodymium gluconate, neodymium citrate, neodymium fumarate, neodymium lactate, neodymium maleate, neodymium oxalate, neodymium 2-ethylhexanoate, neodymium neodecanoate, neodymium naphthenate, neodymium stearate, neodymium oleate, neodymium benzoate, and neodymium picolinate.
[0036] Organic neodymium phosphates include dibutyl neodymium phosphate, diphenyl neodymium phosphate, dihexyl neodymium phosphate, diheptyl neodymium phosphate, dioctyl neodymium phosphate, bis(1-methylheptyl) neodymium phosphate, bis(2-ethylhexyl) neodymium phosphate, didecyl neodymium phosphate, didodecyl neodymium phosphate, dioctadecyl neodymium phosphate, bis(n-nonylphenyl) neodymium phosphate, butyl(2-ethylhexyl) neodymium phosphate, (1-methylphenyl)(2-ethylhexyl) neodymium phosphate and (2-ethylhexyl)(n-nonylphenyl) neodymium phosphate.
[0037] Organic neodymium phosphonates include neodymium butylphosphonate, neodymium pentylphosphonate, neodymium hexylphosphonate, neodymium heptylphosphonate, neodymium octylphosphonate, neodymium (1-methylheptyl)phosphonate, neodymium (2-ethylhexyl)phosphonate, neodymium decylphosphonate, neodymium dodecylphosphonate, neodymium octadecylphosphonate, neodymium oleylphosphonate, neodymium phenylphosphate, neodymium (n-nonylphenyl)phosphonate, neodymium butyl (butylphosphonic acid), neodymium pentyl (pentylphosphate), neodymium hexyl (hexylphosphonic acid), neodymium heptyl (heptylphosphonic acid), neodymium octyl (octylphosphonic acid), neodymium (1-methylheptyl) ((1-methylheptyl)phosphonic acid)), neodymium (2-ethylhexyl) ((2-ethylhexyl)phosphonic acid) Neodymium, decyl(decylphosphonate)neodymium, dodecyl(dodecylphosphonate)neodymium, octadecyl(octadecylphosphonate)neodymium, oleyl(oleylphosphonate)neodymium, phenyl(phenylphosphonate)neodymium, (n-nonylphenyl)((n-nonylphenyl)phosphonate)neodymium, butyl((2-ethylhexyl)phosphonate)neodymium, (2-ethylhexyl)(butylphosphonate)neodymium, (1-methylheptyl)((2-ethylhexyl)phosphonate)neodymium, (2-ethylhexyl)((1-methylheptyl)phosphonate)neodymium, (2-ethylhexyl)((n-nonylphenyl)phosphonate)neodymium and (p-nonylphenyl)((2-ethylhexyl)phosphonate)neodymium.
[0038] Organic neodymium phosphites include neodymium butylphosphite, neodymium amylphosphite, neodymium hexylphosphite, neodymium heptylphosphite, neodymium octylphosphite, neodymium (1-methylheptyl)phosphite, neodymium (2-ethylhexyl)phosphite, neodymium decylphosphite, neodymium dodecylphosphite, neodymium octadecylphosphite, neodymium oleylphosphite, neodymium phenylphosphite, neodymium (n-nonylphenyl)phosphite, neodymium dibutylphosphite, neodymium diamylphosphite, neodymium dihexylphosphite, neodymium diheptylphosphite, neodymium dioctylphosphite. , neodymium bis(1-methylheptyl)phosphite, neodymium bis(2-ethylhexyl)phosphite, neodymium tris-[bis(2-ethylhexyl)phosphite], neodymium didecylphosphite, neodymium didodecylphosphite, neodymium dioctadecylphosphite, neodymium dioleylphosphite, neodymium diphenylphosphite, neodymium bis(n-nonylphenyl)phosphite, neodymium butyl(2-ethylhexyl)phosphite, neodymium (1-methylheptyl)(2-ethylhexyl)phosphite, and neodymium (2-ethylhexyl)(n-nonylphenyl)phosphite.
[0039] Carboxylates of neo acids are most preferred due to their faster and more complete alkylation, which results in a more active catalyst compound.
[0040] Preference is given to using neodymium carboxylates and neodymium organophosphinates, with neodymium neodecanoate and neodymium tris-[bis(2-ethylhexyl)phosphate] or mixtures thereof being most preferred.
[0041] Compounds suitable for use as the organoaluminum compound according to the present invention include trialkylaluminum compounds, triphenylaluminum or dialkylaluminum hydrides, alkylaluminum dihydrides, in particular, trimethylaluminum, triethylaluminum, tri-n-propylaluminum, triisopropylaluminum, tri-n-butylaluminum, triisobutylaluminum, tri-tert-butylaluminum, triphenylaluminum, trihexylaluminum, tricyclohexylaluminum, trioctylaluminum, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride, diisobutylaluminum hydride, dihexylaluminum hydride, diisohexylaluminum hydride, dioctylaluminum hydride, diisooctylaluminum hydride, phenylethylaluminum hydride, phenyl-n-propylaluminum hydride, phenylisopropylaluminum hydride, phenyl-n-butylaluminum hydride, phenylisobutylaluminum hydride, benzylethylaluminum hydride, benzyl-n-butylaluminum hydride, benzylisobutylaluminum hydride, benzylisopropylaluminum hydride, and the like.
[0042] Preferably, an alkylaluminum or an alkylaluminum hydride, or a mixture thereof is used. Most preferred is triethylaluminum, triisobutylaluminum, diisobutylaluminum hydride, or a mixture thereof.
[0043] Compounds used as conjugated dienes according to the present invention include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, piperylene, 2-methyl-3-ethyl-1,3-butadiene, 3-methyl-1,3-pentadiene, 2-methyl-3-ethyl-1,3-pentadiene, 3-methyl-1,3-pentadiene, 1,3-hexadiene, 2-methyl-1,3-hexadiene, 1 ,3-heptadiene, 3-methyl-1,3-heptadiene, 1,3-octadiene, 3-butyl-1,3-octadiene, 3,4-dimethyl-1,3-hexadiene, 4,5-diethyl-1,3-octadiene, phenyl-1,3-butadiene, 2,3-diethyl-1,3-butadiene, 2,3-di-n-propyl-1,3-butadiene and 2-methyl-3-isopropyl-1,3-butadiene.
[0044] The most preferred conjugated dienes are 1,3-butadiene and isoprene.
[0045] Compounds useful as the halogen-containing component in the catalyst composite may include halogenated organic compounds of aluminum and tin, in particular, for example, dimethylaluminum chloride, diethylaluminum chloride, diisobutylaluminum chloride, dimethylaluminum bromide, diethylaluminum bromide, diisobutylaluminum bromide, dimethylaluminum fluoride, diethylaluminum fluoride, diisobutylaluminum fluoride, dimethylaluminum iodide, diethylaluminum iodide, diisobutylaluminum iodide, methylaluminum dichloride, ethylaluminum dichloride, methylaluminum dibromide, ethylaluminum dibromide, methylaluminum difluoride, ethylaluminum difluoride, methylaluminum sesquichloride, ethylaluminum sesquichloride, isobutylaluminum sesquichloride or mixtures thereof, as well as trimethyltin chloride, trimethyltin bromide, triethyltin chloride, triethyltin bromide, di-tert-butyltin dichloride, di-tert-butyltin dibromide, dibutyltin dichloride, dibutyltin dibromide, tributyltin chloride and tributyltin bromide, etc., or mixtures thereof.
[0046] Preferred halogen-containing components are ethylaluminum sesquichloride, ethylaluminum dichloride, diethylaluminum chloride or mixtures thereof.
[0047] The polymerization solvent is an inert organic solvent, such as aliphatic hydrocarbons, in particular, such as butane, pentane, hexane, heptane; alicyclic hydrocarbons, in particular, cyclopentane, cyclohexane; monoolefins, such as 1-butene, 2-butene, or mixtures thereof; aromatic hydrocarbons, in particular, such as benzene, toluene, xylene, which can be used alone or in a mixture with one another.
[0048] According to the proposed process, the most preferred hydrocarbon solvent is a solvent which is a mixture of cyclohexane and hexane or cyclohexane and nefras (commercial grade hexane-heptane fraction of paraffins of dearomatized gasoline obtained by catalytic reforming process, boiling point 65°C to 75°C) in the ratio of (30 to 55)÷(70 to 45).
[0049] The catalyst composite for a polymerization process according to the present invention comprises a lanthanide compound (A), a conjugated diene (B), an organoaluminum compound (C) and a halogen-containing component (D) in a molar ratio of (A):(B):(C):(D) of 1:(5 to 30):(8 to 30):(1.5 to 3.0).
[0050] The preferred molar ratio of the (A) component: (B) component: (C) component: (D) component of the catalyst composite is 1: (5 to 20): (8 to 20): (1.8 to 2.8).
[0051] The most preferred molar ratio of the (A) component:(B) component:(C) component:(D) component of the catalyst composite is 1:(10 to 15):(10 to 15):(2.1 to 2.5).
[0052] The process for preparing diene polymers is a batch or continuous process carried out in a hydrocarbon solvent by feeding a hydrocarbon mixture into a polymerization vessel (reactor / autoclave), wherein the hydrocarbon mixture consists of monomers and a solvent and a catalyst complex premixed with the solvent, wherein the catalyst complex comprises a lanthanide compound, a conjugated diene, an organoaluminum compound and a halogen-containing component. The concentration of the monomers in the solvent is generally 7% to 12% by mass, preferably 9% to 10%. A concentration lower than 7% results in a decrease in the energy efficiency of the process, while a concentration higher than 12% results in an increase in the viscosity of the polymer product, and therefore, results in an increase in energy consumption during separation and drying of the rubber.
[0053] The catalyst complex (CC) is prepared by: introducing an organoaluminum compound (most preferably triisobutylaluminum, triethylaluminum, diisobutylaluminum hydride or a mixture thereof), a lanthanide compound (most preferably a carboxylate, in particular neodecane or tri-[bis(2-ethylhexyl)neodymium phosphate) into a solution of a conjugated diene (most preferably 1,3-butadiene) in an aliphatic solvent; aging the resulting mixture at a temperature of 23±2°C for 2 to 20 hours, and then adding a halogen-containing component (most preferably ethylaluminum sesquichloride, ethylaluminum dichloride, diethylaluminum chloride or a mixture thereof), the molar ratio of the catalyst complex (A): (B): (C): (D) being 1: (5 to 30): (8 to 30): (1,5 to 3,0), wherein (A) is a lanthanide compound, (B) is a conjugated diene, (C) is an organoaluminum compound, and (D) is a halogen-containing component. The dosage of the catalyst complex is calculated based on the monomers (hydrocarbon mixture) and, for component (A), based on the lanthanide (metal), ie, 1.0 mol to 3.0 mol of lanthanide per 1 ton of monomers.
[0054] The polymerization time is 1.5 to 3 hours, and the monomer conversion rate reaches 95% to 99%.
[0055] When a monomer conversion of at least 95% is reached, 2 kg of the polymer product is discharged, an antioxidant solution in an amount of 0.2% to 0.4% by mass based on the polymer is added to stabilize the polymer, degassed and dried on a roller at a temperature of 75° C. to 85° C. The resulting product is used as an unmodified reference sample. The reference polymer has a Mooney viscosity of 30MU to 39MU and is characterized by a linear structure: its branching coefficient, as characterized by the mechanical loss tangent tgδ (1200%), is 9 units to 7 units.
[0056] Then, a branching agent selected from phosphorus-nitrogen compounds and / or halogen-containing compounds is fed to the remaining polymer product. The branching process is carried out at a temperature of 60° C. to 90° C. for 5 minutes to 3 hours, preferably 20 minutes to 1 hour, under constant stirring. At the end of the branching process, 2 kg of the polymer product is discharged, an antioxidant solution is added to the polymer in an amount of 0.2% to 0.4% by mass based on the polymer, degassed and dried on a roller at a temperature of 75° C. to 85° C.
[0057] A modification temperature below 60°C leads to an increase in polymer viscosity, which is undesirable because it adds inevitable difficulties in polymer separation and processing. Meanwhile, at a temperature above 90°C, the terminal groups of the polymer chains tend to lose their activity, and therefore, a high degree of branching of the polymer is impossible.
[0058] Compounds which can be used as branching agents (BA) according to the invention are phosphorus-nitrogen compounds and / or halogen-containing compounds.
[0059] Suitable halogen-containing compounds may include tin compounds, namely tin tetrachloride, methyltin trichloride, dimethyltin dichloride, ethyltin trichloride, diethyltin dichloride, n-butyltin trichloride, di-n-butyltin dichloride, phenyltin trichloride, diphenyltin dichloride, and silicon compounds, such as silicon tetrafluoride, silicon tetrachloride, silicon tetrabromide, and silicon tetraiodide.
[0060] Tin tetrachloride, methyltin trichloride, ethyltin trichloride, butyltin trichloride and silicon tetrachloride are preferred. In the most preferred embodiment, tin tetrachloride and silicon tetrachloride are used.
[0061] The dosage of the branching agent introduced depends on the desired properties of the final product, such as the Mooney viscosity of the polymer, while the increase in the Mooney viscosity of the polymer after its branching (ΔML, %) is between 30% and 40% compared to the unbranched polymer, and the branching index (characterizing the degree of branching of the polymer) characterized by the mechanical loss tangent tgδ (1200%) as measured on an RPA (Rubber Process Analyzer) device at a frequency of 0.1 Hz and a temperature of 100°C changes by 35% to 50% by mass.
[0062] According to the invention, the molar ratio of the halogen-containing compound selected as branching agent BA to the lanthanide is from 1.0 to 20, preferably from 2 to 15, most preferably from 5.0 to 10.0. An increase in the dosage beyond 20.0 moles does not produce an improvement in the polymer properties, but leads to an excessive consumption of BA. A reduction in the molar dosage of less than 1.0 per lanthanide does not change the respective properties of the polymer and the rubber.
[0063] According to the present invention, the phosphorus-nitrogen compound is a compound having a repeating unit based on (-P=N-) n A compound of the chemical structure of wherein n is an integer from 3 to 24. Exemplary compounds used as phosphorus-nitrogen compounds are, but are not limited to, the following:
[0064] 2,2,4,4,6,6-hexachloro-1,3,5-triaza-2,4,6-triphosphorine;
[0065] 2,4,6-Trichloro-2,4,6-triphenoxycyclotriphosphazene;
[0066] 1,1-diphenyl-3,3,5,5-tetramethylaminotriphosphoronitrile;
[0067] 2,2,4,4-tetrachloro-6,6-dimethylmercaptocyclotriphosphazatrien;
[0068] Ethoxypentafluorocyclotriphosphazene;
[0069] (Trifluoroethoxy)pentachlorocyclotriphosphazene;
[0070] Hexafluorocyclotriphosphazene;
[0071] 4,4,6,6-tetrachloro-1,3,5-triaza-2,4,6-triphosphocyclohexa-1,3,5-triene-2,2-diamine;
[0072] 2,4,6-Trichloro-2,4,6-trifluoro-1,3,5-triaza-2λ5,4λ5,6λ5-triphosphane-1,3,5-triene;
[0073] 2,4,6-Trichloro-2,4,6-tris(phenoxy)-1,3,5-triphosphorus;
[0074] trichloride triazide diamide tetrachloride;
[0075] Octachlorocyclotetraphosphazene;
[0076] 1,1-Dimethyl-3,3,5,5-tetrachlorocyclotriphosphazene;
[0077] 2,2,4,4-Tetrachloro-6-isopropyl-2λ5,4λ5,6λ5-[1,3,5,2,4,6]triazatriphenylphosphine (triphosphinine);
[0078] 1-Methyl-1,3,3,5,5-pentachlorocyclotriphosphazene;
[0079] 1,3,5,2,4,6-Triazatriphosphabenzene, 2,4,6-tribromo-2,4,6-trifluoropolymer dialdehyde;
[0080] 4,6-difluoro-2-N,N-2,2-N'2-N',4-N,4-N,N-6,6-N-octamethyl-1,3,5-triaza-2λ5,4λ5,6λ5-triphospha-cyclohexa-1,3,5-triene-2,2,4,6-tetraamine;
[0081] 2,2,4,4,6,6-hexahydro-2,2,4,4,6,6-hexapropoxy-propoxy-1,2,3,4,5,6-triazatriphosphabenzene;
[0082] 1,1-Diphenyl-3,3,5,5-tetramethylamino-triphosphazene, etc.
[0083] In a preferred embodiment, chlorine-containing phosphorus-nitrogen compounds are used which contain 2 to 6 chlorine atoms.
[0084] In the most preferred embodiment, the compound used is: 2,2,4,4,6,6-hexachloro-1,3,5-triaza-2,4,6-triphosphazene; 2,4,6-trichloro-2,4,6-triphenoxy cyclotriphosphazene; 2,2,4,4-tetrachloro-6,6-dimethylmercaptocyclotriphosphazene; 4,4,6,6-tetrachloro-1,3,5-triaza-2,4,6-triphosphacyclohexa-1,3,5-triene-2,2-diamine or a mixture thereof.
[0085] According to the present invention, the dosage of the phosphorus-nitrogen compound selected as BA is 0.5 mol to 15.0 mol per mol of lanthanide. An increase in the dosage of more than 15.0 based on the molar dosage of the lanthanide does not lead to an improvement in the properties of the polymer and rubber, but results in excessive consumption of the modifier. A decrease in the dosage of less than 0.5 based on the molar dosage of the lanthanide does not improve the respective properties of the polymer and rubber.
[0086] The most preferred dosage of the chlorine-containing phosphorus-nitrogen compound is 1.0 mol to 5.0 mol per 1 mol of the lanthanide element, because this modifier dosage allows optimum properties of the polymer and the rubber based on the polymer to be achieved with relatively small consumption of the modifier.
[0087] The resulting branched polymer is characterized by a Mooney viscosity of 44MU to 53MU and a branching index as characterized by the mechanical loss tangent tgδ (1200%) of 4.0 to 5.0. In addition, the increase in Mooney viscosity of the branched polymer relative to the unmodified reference sample is in the range of 30% to 50%.
[0088] The increase in viscosity (%) was calculated by the following formula:
[0089] ΔML 2 / 1 =(ML2-ML1) / ML1*100,
[0090] Where ΔML 2 / 1 is the increase in Mooney viscosity of the branched polymer relative to the linear polymer;
[0091] ML2 is the Mooney viscosity of the branched polymer;
[0092] ML1 is the Mooney viscosity of the linear polymer;
[0093] The change in polymer branching (%) was calculated by the following formula:
[0094] Δtgδ1200% 2 / 1 =(tgδ1200%2-tgδ1200%1) / tgδ1200%1*100,
[0095] Where Δtgδ1200% 2 / 1 is the change in branching of the polymer relative to the linear polymer;
[0096] tgδ1200%2 is the branching index of the branched polymer expressed as the mechanical loss tangent determined at a variable amplitude of 0% to 1200%, a frequency of 0.1 Hz and a temperature of 100°C;
[0097] tgδ1200%1 is the branching index of a linear polymer expressed as the mechanical loss tangent determined with a variable amplitude ranging from 0% to 1200%, a frequency of 0.1 Hz and a temperature of 100°C.
[0098] Furthermore, a solution of 0.2 to 0.4 mass % of an antioxidant based on the amount of the polymer and 0.5 to 5.0 mass % of a plasticizer which is a low molecular weight polymer having a molecular weight of 1500 to 5000 g / mol based on the amount of the polymer is introduced into the remaining polymer product, stirred for 5 to 10 minutes, degassed and dried on a roll at a temperature of 75° C. to 85° C.
[0099] The dosage of plasticizer is calculated so that the viscosity of the polymer does not drop by more than 10% after the introduction of the plasticizer and the branching index does not change by more than 10%. Otherwise, the conditional tensile strength is deteriorated.
[0100] The decrease in viscosity ML3 / 2 is calculated by the following formula:
[0101] ΔML 3 / 2 =(ML2-ML3) / ML2*100,
[0102] Where ΔML 3 / 2 is the decrease in Mooney viscosity of the polymer;
[0103] ML2 is the Mooney viscosity of the branched polymer;
[0104] ML3 is the Mooney viscosity of the branched and plasticizer-modified polymer.
[0105] The change in polymer branching (%) was calculated by the following formula:
[0106] Δtgδ 1200%3 / 2=(tgδ1200%3-tgδ1200%2) / tgδ1200%2*100,
[0107] Where Δtgδδ1200%3 / 2 is the change in polymer branching;
[0108] tgδ1200%2 is the branching index of the branched polymer expressed as the mechanical loss tangent determined at a variable amplitude of 0% to 1200%, a frequency of 0.1 Hz and a temperature of 100°C;
[0109] tgδ 1200%3 is the branching index of the branched and modified polymers expressed as the mechanical loss tangent determined at a variable amplitude of 0% to 1200%, a frequency of 0.1 Hz and a temperature of 100°C.
[0110] The rubber composition was processed on a roll after kneading, wherein the preparation of the rubber composition for vulcanization, the vulcanization and the preparation of the test specimens were performed according to ASTM D 3182 and ASTM D 3189. The ASTM D 3189 formulation is presented in Table 1.
[0111] The branched polydiene prepared according to the invention has a Mooney viscosity index of 40 MU to 49 MU, a polydispersity index in the range of 2.16 to 2.60, a branching index as characterized by the mechanical loss tangent tgδ (1200%) of 4.7 to 5.3, wherein the content of 1,4-cis units is 96.0% to 98.0%. The rubber mixture obtained based on the prepared polydiene is characterized by a low Mooney viscosity, a good distribution of fillers in the polymer matrix and good elastic-hysteresis properties (i.e. ML (1+4), MU, Payne effect Δ (G'1%-G'50%), kPa, tgδ at 10% deformation at 60°C).
[0112] The use of BA and plasticizer according to the invention provides branched polydienes which show better processability results and better elastic-hysteresis properties in tests of rubber compositions compared to unmodified polymers, polymers modified with only one BA or a mixture thereof but without a plasticizer, and compared to polymers prepared using only a plasticizer.
[0113] Table 1. Rubber compound formulation (ASTM 3189)
[0114] Element Weight Butadiene rubber 100.0 Carbon Black N330(IRB 8) 60.0 Zinc oxide paint 3.0 Commercial grade stearic acid 2.0 Naphthenic Oil 15.0 Gas sulfur 1.5 Sulfenamide T 0.9 total: 182.40
[0115] Embodiments of the invention
[0116] The following discloses embodiments of the present invention. It will be appreciated by those skilled in the art that the present invention is not limited to the embodiments presented alone, and that the same effects may be achieved with other embodiments without exceeding the purpose of the claimed invention.
[0117] Disclosed below are test methods used to evaluate the properties of polymers prepared by the claimed process.
[0118] 1. The percent conversion was determined gravimetrically by precipitating the polymer from the polymerization product with ethanol, drying the separated polymer and calculating the weight fraction of the polymer in the polymerization product.
[0119] 2. Molecular weight properties of rubbers The molecular weight properties of rubbers were measured using gel permeation chromatography using a gel chromatograph (Waters Breeze System) with a refractometer according to the method provided by the inventors of the present invention. The rubber samples were dissolved in freshly distilled tetrahydrofuran, and the weight concentration of the polymer in the solution was 2 mg / ml; a universal calibration was performed using polystyrene standards. The Kuhn-Mark-Houwink constants (K=0.00041, α=0.693) were used to calculate the polydiene. Test conditions:
[0120] - A set of 4 high-resolution columns (length 300 mm, diameter 7.8 mm) equipped with Styragel (HR3, HR4, HR5, HR6), which allows the analysis of molecular weights from 500 amu to 1×10 7 polymers of amu;
[0121] -Flow rate is 1cm 3 / min of tetrahydrofuran solvent;
[0122] - The temperature of the thermostat column and refractometer is 3000°C.
[0123] 3. Mooney viscosity is determined according to ASTM D 1646.
[0124] 4. Elastic component used to evaluate the distribution of fillers in rubber compositions and the silanization of fillers The complex dynamic shear modulus G' (kPa) was determined on an RPA-2000 Rubber Processing Analyzer (Alpha Technologies) at 0.1 Hz and 100° C. over a deformation range of 1% to 450%. The difference between the storage moduli measured at 1% and 50% strain amplitudes is CG'=(G'1%-G'43%), i.e., the Payne effect.
[0125] 5. The branching index characterized by the mechanical loss tangent tgδ (1200%) was determined on an RPA-2000 Rubber Processability Analyzer (Alpha Technologies) using the following test mode: the change in tgδ was evaluated within a variable shear amplitude in the amplitude range of 10% to 1200% at a frequency of 0.1 Hz and a temperature of 100°C.
[0126] Example 1 (based on prototype)
[0127] Butadiene (BD) is polymerized in a hydrocarbon solvent in the presence of a catalyst complex prepared on the basis of neodymium versatate (Nd), followed by the addition of diisobutylaluminum hydride (DIBAG) as an alkylating agent, diethylaluminum chloride (DEAC), neodymium versatate (NdV3), and diisobutylaluminum hydride (DIBAH) as a halogen donor. DIBAH is used in an 8-fold molar excess relative to the neodymium dosage, while DEAC is used in a 3-fold molar excess. The dosage of the catalyst complex is 2.8 mol of neodymium per 1 ton of butadiene (BD). The polymerization is carried out in a 20-liter reactor equipped with a mixing device and a jacket for heat removal. The polymerization process lasts for 90 minutes. At the end of the polymerization, 2 liters of the polymer product are discharged from the reactor; the monomer conversion is 98%. A phenolic antioxidant (Irganox 1520) is added to the selected aliquot in an amount of 0.06% by mass. The solvent is removed and rolling is performed at a temperature of 80°C. The branching coefficient of the polymer and the molecular weight characteristics (MMC) measured by GPC are determined in selected aliquots; the Mooney viscosity of the prepared linear polymer is 35MU. At a temperature of 90°C, a solution of maleated polybutadiene Ricon 130MA8 in a mixture of hexane (the concentration of the solution is 0.15 mol / L) is fed to the remaining polymerization product in the reactor at a dosage of 1.2 mol per Nd. After 10 minutes, the primary antioxidant (Irganox565) and the secondary antioxidant (TNPP) are added, and the resulting modified polymer is discharged. The Mooney viscosity of the modified polymer is 43MU and tgδ1200%=5.567, i.e. the polymer obtained is branched.
[0128] Example 2 (Comparative)
[0129] Butadiene (BD) is polymerized in a hydrocarbon solvent in the presence of the following catalyst complex formed in advance: neodymium neodecanoate-butadiene (BD)-diisobutylaluminum hydride (DIBAH)-ethylaluminum sesquichloride (EASC) in a component molar ratio of 1:10:12:2.5. The aging time of the complex at a temperature of 23°C is 22 hours. The polymerization is carried out in a 20-liter reactor. The dried residue is equal to 11%. The dosage of the catalyst complex is 1.8 mol of neodymium per 1 ton of butadiene (BD). After achieving a conversion rate of more than 95% based on the monomer, 2 kg of the polymer product are discharged, a solution of a phenolic antioxidant is introduced in an amount of 0.3% by mass based on the polymer to stabilize the polymer, degassed and dried on a roller at a temperature of 75°C to 85°C. Afterwards, the physical and mechanical properties and the molecular weight properties are determined (Table 3). To the remaining polymer, an antioxidant solution at a dosage of 0.3 mass % based on the polymer and a low molecular weight polybutadiene Polyvest 130 at a dosage of 0.8 mass % (8 g per kg of polybutadiene) were added, stirred for 10 minutes, degassed and dried on a roller at a temperature of 80° C. The physical and mechanical properties, molecular weight properties, increase in polymer viscosity and change in branching coefficient (mechanical loss tangent tgδ(1200%)) are shown in Table 3.
[0130] Example 3 (Comparative)
[0131] Butadiene (BD) is polymerized in a hydrocarbon solvent in the presence of the following catalyst complex: neodymium neodecanoate-butadiene (BD)-diisobutylaluminum hydride (DIBAH)-ethylaluminum sesquichloride (EASC) in a component molar ratio of 1:10:11:2.5. The aging time of the complex is 20 hours at a temperature of 24°C. The dosage of the catalyst complex is 1.7 mol of neodymium per 1 ton of butadiene (BD).
[0132] After achieving a conversion of more than 95% based on the monomer, the branching agent 2,2,4,4,6,6-hexachloro-1,3,5-triaza-2,4,6-triphosphabenzene (HCF) was fed in a dosage of 1.0 mol based on neodymium. The modification process was continued for 60 minutes at a temperature of 80° C. under constant stirring, and then 2 kg of the polymer product was discharged, an antioxidant solution was introduced in an amount of 0.4% by mass based on the polymer, degassed and dried on a roller at a temperature of 80° C. The properties of the polymer obtained are shown in Table 3.
[0133] Example 4 (according to the present invention)
[0134] Butadiene (BD) is polymerized in a hydrocarbon solvent in the presence of the following catalyst complex: neodymium neodecanoate-butadiene (BD)-diisobutylaluminum hydride (DIBAH)-ethylaluminum sesquichloride (EASC) in a component molar ratio of 1:10:13:2.5, wherein the amount of neodymium neodecanoate is given based on the amount of neodymium. The dosage of the catalyst complex is 1.7 mol of neodymium per 1 ton of butadiene (BD). After achieving a conversion rate of more than 95% based on the monomer, 2 kg of the polymer product was discharged, a phenolic antioxidant solution was introduced in an amount of 0.3% by mass based on the polymer to stabilize the polymer, degassed and dried on a roller at a temperature of 75° C. (step 1), a branching agent 2,2,4,4,6,6-hexachloro-1,3,5-triaza-2,4,6-triphosphabenzene (HCF) was fed to the remaining polymer in an amount of 1.3 mol per 1 mol of neodymium, 2 kg of the polymer product was discharged, an antioxidant solution was introduced therein in an amount of 0.4% by mass based on the polymer, degassed and dried on a roller at a temperature of 80° C. (step 2). To the remaining polymer, an antioxidant solution in an amount of 0.4% by mass based on the polymer and a low molecular weight polybutadiene Polyvest 130 in an amount of 1.5% by mass (15 g per kg of polybutadiene) were added, stirred for 10 minutes, degassed and dried on a roller at a temperature of 80° C. (step 3). The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0135] Example 5
[0136] The procedure is similar to Example 4, except that 2,4,6-trichloro-2,4,6-triphenoxycyclotriphosphazene (THF) is used as branching agent in a dosage of 1.5 mol per 1 mol of neodymium. The modification process is continued at a temperature of 80° C. for 60 minutes with constant stirring.
[0137] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0138] Example 6
[0139] The process is similar to Example 4, except that 2,4,6-trichloro-2,4,6-triphenoxycyclotriphosphazene (THF) is used as a branching agent (step 2) at a dosage of 1.8 mol based on neodymium. Polyvest EP-ST-E 60 is used as a plasticizer at a dosage of 0.8 mass % (8 g per kg of polybutadiene) and stirred for 5 minutes.
[0140] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0141] Example 7
[0142] The process is similar to Example 4, except that the catalyst composite is prepared based on gadolinium versatate (GdV3). The dosage of the branching agent (HCF) is 1.5 mol per 1 mol of gadolinium. Liquid polyisoprene LIR 50 is used as a plasticizer in step 3 at a dosage of 0.8 mass % based on the polymer (8 g per 1 kg of polybutadiene).
[0143] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0144] Example 8
[0145] The process is similar to Example 5, except that the prepared catalyst composite contains neodymium tris-[bis(2-ethylhexyl)phosphate] (NdP3), butadiene (BD) and diisobutylaluminum hydride (DIBAH); and ethylaluminum sesquichloride (EASC) is used as the chlorinating agent. The molar ratio of the BD:Nd:DIBAH:EASC components of the catalyst composite is 10:1:15:2.7. The composite is aged for 22 hours at a temperature of 25°C.
[0146] In step 2, 1,1-diphenyl-3,3,5,5-tetramethylaminotriphosphazene (DPP) was used as a branching agent in an amount of 0.5 mmol per 1 mol of neodymium.
[0147] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0148] Example 9
[0149] The process is similar to Example 7, except that the prepared catalyst composite contains neodymium tris-[bis(2-ethylhexyl)phosphate] (NdP3), butadiene (BD) and diisobutylaluminum hydride (DIBAH); and ethylaluminum sesquichloride (EASC) is used as the chlorinating agent. The molar ratio of the BD:Nd:DIBAH:EASC components of the catalyst composite is 10:1:15:2.7. The composite is aged for 22 hours at a temperature of 25°C.
[0150] 1,1-Diphenyl-3,3,5,5-tetramethylaminotriphosphazene (DPP) was used as a branching agent in an amount of 1.5 mmol per 1 mol of neodymium in step 2. Liquid polyisoprene LIR 30 was used as a plasticizer in a dosage of 1.0 mass % based on the polymer (10 g per 1 kg of polybutadiene) in step 3.
[0151] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0152] Example 10
[0153] The process is similar to Example 8, except that the prepared catalyst composite contains praseodymium versatate (PrV3), butadiene (BD) and diisobutylaluminum hydride (DIBAH) and ethylaluminum sesquichloride (EASC). The molar ratio of BD:Nd:DIBAH:EASC components of the catalyst composite is 10:1:11:2.2. The composite is aged for 19 hours at a temperature of 22°C.
[0154] HCF was used as a branching agent in a dosage of 0.2 mol per 1 mol of praseodymium. Liquid polyisoprene LIR 30 was used as a plasticizer in step 30 in a dosage of 1.5 mass % based on the polymer (15 g per 1 kg of polybutadiene).
[0155] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0156] Embodiment 11
[0157] The process is similar to Example 8, except that HCF is used as a branching agent in a dosage of 1.8 mol per 1 mol of neodymium (step 2). Polyvest EP-ST-E 80, a liquid polybutadiene functionalized with triethoxysilane having a silanization degree of 80%, is used as a plasticizer in an amount of 1.0 mass % based on the polymer (10 g per 1 kg of polybutadiene).
[0158] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0159] Example 12
[0160] The procedure is similar to Example 10, except that a liquid polybutadiene functionalized with triethoxysilane, Polyvest EP-ST-E 80, having a silanization degree of 100% is used as plasticizer in an amount of 1.5% by mass based on the polymer (15 g per 1 kg of polybutadiene).
[0161] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0162] Embodiment 13
[0163] The procedure was similar to Example 10, except that the dosage of the branching agent was 1.2 mol per 1 mol of neodymium, and maleated liquid rubber Ricon 131MA10 was used as a plasticizer in an amount of 0.8 mass % based on the polymer (8 g per 1 kg of polybutadiene).
[0164] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0165] Embodiment 14
[0166] The procedure was similar to Example 8, except that the dosage of the branching agent DFF was 5.0 mol per 1 mol of neodymium. Non-functionalized liquid polybutadiene Polyvest EP-ST-E130 was used as a plasticizer in an amount of 2 mass % based on the polymer (20 g per 1 kg of polybutadiene).
[0167] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0168] Embodiment 15
[0169] The procedure was similar to Example 13, except that thionyl chloride (SOCl2) was used as a branching agent in an amount of 5 mol per 1 mol of neodymium.
[0170] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0171] Example 16
[0172] The procedure was similar to Example 11, except that thionyl chloride was used as a branching agent in an amount of 7.0 mol per 1 mol of neodymium, and maleated liquid rubber Ricon 130MA 8% was used as a plasticizer in an amount of 1.5 mass % based on the polymer (15 g per 1 kg of polybutadiene).
[0173] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0174] Embodiment 17
[0175] The procedure was similar to Example 14, except that tin tetrachloride (SnCl4) was used as a branching agent at a dosage of 2.5 mol per 1 mol of neodymium.
[0176] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0177] Embodiment 18
[0178] The process is similar to Example 14, except that tin tetrachloride (SnCl4) is used as a branching agent in a dosage of 5.0 mol per 1 mol of neodymium, and liquid polybutadiene Polyvest EP-ST-E 80 functionalized with triethoxysilane having a silanization degree of 100% is used as a plasticizer in an amount of 5 mass % based on the polymer (50 g per 1 kg of polybutadiene).
[0179] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0180] Embodiment 19
[0181] The procedure is similar to Example 9, except that the catalyst composite is prepared based on neodymium tris-[(2-ethyl)hexanoate] (NdEh3), the dosage of DFF is 15 mol per 1 mol of neodymium (step 2), and in step 3 the dosage of plasticizer LIR 30 is 0.5% by mass based on the polymer (5 g per 1 kg of polybutadiene).
[0182] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0183] Embodiment 20
[0184] The procedure is similar to Example 18, except that the catalyst composite is prepared based on neodymium tris-[bis(2-ethylhexyl)phosphate], the dosage of tin tetrachloride used as branching agent is 20 mol per 1 mol of neodymium, and Ricon 131MA10 is used as plasticizer in a dosage of 0.5 mass % based on the polymer (5 g per 1 kg of polybutadiene).
[0185] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0186] Embodiment 21
[0187] The process is similar to Example 19, except that the catalyst composite is prepared based on neodymium neodecanoate. The molar ratio of the BD:Nd:DIBAH:EASC components of the catalyst composite is 10:1:13:2.0. The composite is aged for 19 hours at a temperature of 22°C. The dosage of branching agent SiCL4 is 1.0 mol per 1 mol of neodymium; Polyvest EP-ST-E MA75 is used as a plasticizer at a dosage of 0.5 mass % based on the polymer (5 g per 1 kg of polybutadiene).
[0188] The physical and mechanical properties and molecular weight properties of the polymers obtained in different steps are shown in Table 3.
[0189] The samples of the polymers obtained in Examples 1 to 22 were tested in the formulation of rubber compositions (ASTM 3189). The test results are shown in Table 4.
[0190]
[0191] Notes:
[0192] Polyvest EP-ST-E 60 - liquid polybutadiene functionalized with triethoxysilane, degree of silanization 60%
[0193] Polyvest EP-ST-E 80 - Liquid polybutadiene functionalized with triethoxysilane, degree of silanization 80%
[0194] Polyvest EP-ST-E 100 - Liquid polybutadiene functionalized with triethoxysilane, 100% silanization
[0195] Polyvest 130(S) - Non-functionalized liquid polybutadiene(S), contains antioxidant
[0196] Polyvest EP-ST-E MA75 - Liquid polybutadiene functionalized with maleic anhydride
[0197] LIR 30 - Liquid polyisoprene, 30% silanization
[0198] LIR 50 - Liquid polyisoprene, 50% silanization
[0199] Ricon 130MA8 - Liquid polybutadiene with 8 maleic acid groups functionalized with maleic anhydride
[0200] Ricon 131MA10 - Liquid polybutadiene with 10 maleic acid groups functionalized with maleic anhydride
[0201]
[0202]
[0203]
[0204]
[0205]
[0206] Notes:
[0207] *- For branching agents, the dosage is given in moles per 1 mol of lanthanide; for plasticizers, the dosage is given in mass % based on 100% polymer
[0208] Abbreviations used in Table 3:
[0209] NdP3-tris-[bis(2-ethylhexyl)phosphate]neodymium
[0210] NdV3-neodymium neodecanoate
[0211] GdV3-gadolinium tert-carbonate
[0212] NdEh3 – Neodymium tris-[(2-ethyl)hexanoate]
[0213] DEAC-Diethylaluminum chloride
[0214] EASC-Ethylaluminum Sesquichloride
[0215] HCP-2,2,4,4,6,6-hexachloro-1,3,5-triaza-2,4,6-triphosphabenzene;
[0216] TCP-2,4,6-trichloro-2,4,6-triphenoxycyclotriphosphazene;
[0217] DPP-1,1-diphenyl-3,3,5,5-tetramethylaminotriphosphazene;
[0218] SiCL4-Silicon Tetrachloride
[0219] SOCl2-Thionyl chloride
[0220] ΔML 2 / 1 (%) - the increase in viscosity of the polymer obtained in step 2 compared to the polymer obtained in step 1 calculated by the formula provided in the "Summary of the Invention" section
[0221] Δtgδ1200%2 / 1 (%) - the change in the branching index of the polymer obtained in step 2 compared to the polymer obtained in step 1 calculated by the formula provided in the "Summary of the Invention" section,
[0222] ΔML 3 / 2 (%) - the decrease in Mooney viscosity of the branched polymer obtained in step 2 after the introduction of the plasticizer (step 3), calculated by the formula provided in the "Summary of the Invention" section,
[0223] Δtgδ1200%3 / 2(%) - Change in the branching index of the polymer obtained in step 3 compared to the polymer obtained in step 2 calculated by the formula provided in the "Summary of the Invention" section
[0224]
[0225]
[0226] As can be seen from Table 4, the proposed method for preparing branched polydienes can improve the processability of the rubber composition by 6% to 10% (based on the Mooney viscosity index) and can improve the distribution of fillers in the polymer matrix (assessed by Payne effect parameters).
[0227] When only a modifier is used without a plasticizer, a desired range of branching index tgδ (1200%) of about 4.7 to about 5.3 cannot be achieved, and thus, processability of the rubber composition and distribution of fillers in such a polymer are poor.
[0228] Thus, the technical solution according to the invention allows the production of branched polydiene characterized by a Mooney viscosity of about 40 MU to about 49 MU and a branching index characterized by the mechanical loss tangent tgδ (1200%) of about 4.7 to about 5.3. The polydiene prepared according to the invention has improved processability, improved distribution of fillers in the polymer matrix, and the rubber composition based on the polydiene is characterized by improved elastic-hysteresis properties (i.e., Mooney viscosity ML (1+4), MU, Payne effect Δ (G'1%-G'50%), kPa, tgδ at 60°C 10% deformation).
Claims
1. A branched polydiene, comprising a halogen-containing compound selected from a tin or silicon atom; having a repeating unit (-P=N-) n or a mixture thereof, and then modified by introducing 0.7% to 5.0% by mass of at least one plasticizer based on the polymer, wherein the plasticizer is a non-functionalized low molecular weight polybutadiene or polyisoprene with a molecular weight of 1500 g / mol to 50000 g / mol, a low molecular weight polybutadiene functionalized with maleic anhydride or triethoxysilane with a molecular weight of 1500 g / mol to 50000 g / mol, or a low molecular weight polyisoprene functionalized with maleic anhydride with a molecular weight of 1500 g / mol to 50000 g / mol, and characterized in that A Mooney viscosity of 40 to 49 Mooney units, and a branching index expressed as a mechanical loss tangent tgδ1200% of 4.7 to 5.3, the mechanical loss tangent tgδ1200% being measured using a variable shear amplitude within an amplitude range of 10% to 1200%, a frequency of 0.1 Hz and a temperature of 100°C.
2. A method for producing the branched polydiene according to claim 1 by polymerization of a conjugated diene, comprising: preparing a catalyst composite comprising a lanthanide compound, an organoaluminum compound, a conjugated diene, and a halogen-containing component; polymerizing the conjugated diene in the presence of the catalyst complex; post-polymerization modification with at least one branching agent selected from halogen-containing compounds, phosphorus-nitrogen compounds, or mixtures thereof; Termination; Introducing at least one plasticizer into the polymer, wherein the plasticizer is a low molecular weight polymer having a molecular weight of 1500 g / mol to 5000 g / mol and the dosage of the plasticizer is 0.7% to 5.0% by mass based on the polydiene; The polymer was degassed and dried.
3. The method according to claim 2, characterized in that The branching agent is a halogen-containing compound selected from the group consisting of thionyl chloride, diphenyltin dichloride, phenyltin trichloride, triphenyltin chloride, dibutyltin dichloride, butyltin trichloride, tin tetrachloride or silicon tetrachloride.
4. The method according to claim 2, characterized in that The branching agent is a halogen-containing compound, and the halogen-containing compound is selected from tin tetrachloride, methyltin trichloride, ethyltin trichloride, butyltin trichloride or silicon tetrachloride.
5. The method according to claim 2, characterized in that The branching agent is a halogen-containing compound, and the halogen-containing compound is selected from tin tetrachloride or silicon tetrachloride.
6. The method according to claim 2, characterized in that The molar ratio of the halogen-containing compound selected as the branching agent to the lanthanide element is 1.0 to 20.
7. The method according to claim 2, characterized in that The molar ratio of the halogen-containing compound selected as the branching agent to the lanthanide element is 2.0 to 15.
8. The method according to claim 2, characterized in that The molar ratio of the halogen-containing compound selected as the branching agent to the lanthanide element is 5.0 to 10.
0.
9. The method according to claim 2, characterized in that The branching agent is the phosphorus-nitrogen compound containing 2 to 6 chlorine atoms.
10. The method according to claim 2, characterized in that The branching agent is a chlorine-containing phosphorus-nitrogen compound selected from the group consisting of: 2,2,4,4,6,6-hexachloro-1,3,5-triaza-2,4,6-triphosphazene; 2,4,6-trichloro-2,4,6-triphenoxy cyclotriphosphazene; 2,2,4,4-tetrachloro-6,6-dimethylmercaptocyclotriphosphazene or 4,4,6,6-tetrachloro-1,3,5-triaza-2,4,6-triphosphacyclohexa-1,3,5-triene-2,2-diamine.
11. The method according to claim 2, characterized in that The dosage of the phosphorus-nitrogen compound selected as the branching agent is 0.5 mol to 15.0 mol per 1 mol of the lanthanide element.
12. The method according to claim 2, characterized in that The dosage of the phosphorus-nitrogen compound selected as the branching agent is 1.0 mol to 5.0 mol per 1 mol of the lanthanide element.
13. The method according to claim 2, characterized in that The plasticizer is a non-functionalized low molecular weight polybutadiene, a polybutadiene functionalized with maleic anhydride or triethoxysilane, a non-functionalized low molecular weight polyisoprene, or a polyisoprene functionalized with maleic anhydride.
14. The method according to claim 2, characterized in that The plasticizer is a non-functionalized low molecular weight polybutadiene or a polybutadiene functionalized with maleic anhydride or triethoxysilane.
15. The method according to claim 2, characterized in that The dosage of the plasticizer is 0.7% to 2.0% by mass based on the polymer.
16. The method according to claim 2, characterized in that The dosage of the plasticizer is 0.8% to 1.5% by mass based on the polymer.
17. The method according to claim 2, characterized in that The lanthanide compound in the catalyst composite is neodymium carboxylate or neodymium organophosphate.
18. The method according to claim 17, characterized in that The lanthanide compound in the catalyst composite is neodymium neodecanoate, neodymium tris-[bis(2-ethylhexyl)phosphate], or a mixture thereof.
19. The method according to claim 2, characterized in that The organoaluminum compound is a compound selected from the group consisting of trialkylaluminum, triphenylaluminum, dialkylaluminum hydride, and alkylaluminum dihydride.
20. The method according to claim 2, characterized in that The organoaluminum compound is a compound selected from the following: trimethylaluminum, triethylaluminum, tri-n-propylaluminum, triisopropylaluminum, tri-n-butylaluminum, triisobutylaluminum, tri-tert-butylaluminum, triphenylaluminum, trihexylaluminum, tricyclohexylaluminum, trioctylaluminum, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride, diisobutylaluminum hydride, dihexylaluminum hydride, diisohexylaluminum hydride, dioctylaluminum hydride, diisooctylaluminum hydride, phenylethylaluminum hydride, phenyl-n-propylaluminum hydride, phenylisopropylaluminum hydride, phenyl-n-butylaluminum hydride, phenylisobutylaluminum hydride, benzylethylaluminum hydride, benzyl-n-butylaluminum hydride, benzylisobutylaluminum hydride, and benzylisopropylaluminum hydride.
21. The method according to claim 2, characterized in that The organoaluminum compound is a compound selected from the group consisting of triethylaluminum, triisobutylaluminum, diisobutylaluminum hydride or a mixture thereof.
22. The method according to claim 2, characterized in that The conjugated diene is a compound selected from the group consisting of 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, piperylene, 2-methyl-3-ethyl-1,3-butadiene, 3-methyl-1,3-pentadiene, 2-methyl-3-ethyl-1,3-pentadiene, 1,3-hexadiene, 2-methyl-1,3-hexadiene, 1,3-heptadiene, 3-methyl-1,3-heptadiene, 1,3-octadiene, 3-butyl-1,3-octadiene, 3,4-dimethyl-1,3-hexadiene, 4,5-diethyl-1,3-octadiene, phenyl-1,3-butadiene, 2,3-diethyl-1,3-butadiene, 2,3-di-n-propyl-1,3-butadiene, and 2-methyl-3-isopropyl-1,3-butadiene.
23. The method according to claim 2, characterized in that The conjugated diene is a compound selected from 1,3-butadiene and isoprene.
24. The method according to claim 2, characterized in that The catalyst composite for polymerization comprises a lanthanide compound (A), a conjugated diene (B), an organoaluminum compound (C) and a halogen-containing component (D) in a molar ratio of (A):(B):(C):(D) of 1:(5 to 30):(8 to 30):(1.5 to 3.0), wherein the molar amount of the lanthanide compound (A) is calculated based on the molar amount of the lanthanide.
25. A branched polydiene prepared by the process of claim 2.
26. A rubber mixture based on the branched polydiene according to any one of claims 1 or 25.
Citation Information
Patent Citations
Natural rubber mixture with improved low temperature flexibility
EP2082899A1
Rubber composition for tires and pneumatic tire
US6472461B1
Process for the preparation of low branch content polybutadiene
US7112632B2
Tread rubber compounds having improved abrasion resistance using functionalized liquid polybutadiene
US8975324B2
Method for producing functionalized cis-1,4-polydienes having high cis-1,4-linkage content and high functionality
CN101225134A